Synthesis methods and applications of palladium nanoparticles: A review - Joudeh, Nadeem; Saragliadis, Athanasios; Koster, Gerbrand; Mikheenko, Pavlo; Linke, Dirk (Frontiers in Nanotechnology, 2022)
Palladium (Pd) is a key component of many catalysts. Nanoparticles (NPs) offer a larger surface area than bulk materials, and with Pd cost increasing 5-fold in the last 10 years, Pd NPs are in increasing demand. Due to novel or enhanced physicochemical properties that Pd NPs exhibit at the nanoscale, Pd NPs have a wide range of applications not only in chemical catalysis, but also for example in hydrogen sensing and storage, and in medicine in photothermal, antibacterial, and anticancer therapies. Pd NPs, on the industrial scale, are currently synthesized using various chemical and physical methods. The physical methods require energy-intensive processes that include maintaining high temperatures and/or pressure. The chemical methods usually involve harmful solvents, hazardous reduction or stabilization agents, or produce toxic pollutants and by-products. Lately, more environmentally friendly approaches for the synthesis of Pd NPs have emerged. These new approaches are based on the use of the reducing ability of phytochemicals and other biomolecules to chemically reduce Pd ions and form NPs. In this review, we describe the common physical and chemical methods used for the synthesis of Pd NPs and compare them to the plant- and bacteria-mediated biogenic synthesis methods. As size and shape determine many of the unique properties of Pd NPs on the nanoscale, special emphasis is given to the control of these parameters, clarifying how they impact current and future applications of this exciting nanomaterial.